Perancangan Sistem Pendataan Stok pada CV Mercu Husada Indonesia Berbasis Web - Muhammad Hanif Fauzan (ALMUISY: Journal of Al Muslim Information System, 2024)
Stock data collection manually using paper and document media will reduce the efficiency of stock renewal activities carried out within a certain period of time. Data irrelevance is also one of the main problems in manual data collection. Where the number of goods in the warehouse is not the same as the data in the report book. The application at CV Mercu Husada Indonesia is based on the need for precise and accurate information management in managing the status of goods in the warehouse. The author uses data flow diagrams to design workflow schemes for this system and ERD to create relationships between tables. Before creating this information system, the authors designed the tables needed in advance to make it easier to manufacture. This information system was created using the programming language PHP and MySQL as the database. The result of this study is the application of inventory data collection, which can facilitate the activity of goods data collection and speed up the process of conveying inventory information.